Importancia nutricional en postlarvas de camarón litopenaeus vannamei a nivel de laboratorio con balanceado al 40% de proteina - Quichimbo Quezada, Juan Daniel (Machala : Universidad Técnica de Machala, 2022)
The culture of Litopenaeus vannamei shrimp plays a very important role in the economy of Ecuador, since it generates jobs for many families. The culture at laboratory level is of great relevance and very complex, since many important factors must be controlled for the development of the organisms, among which are the physical, chemical and biological parameters, This bibliographic review focuses on analyzing the relationship between the aforementioned parameters for better survival and growth, in addition to emphasizing the importance of balanced feed in Litopenaeus vannamei shrimp postlarvae, and the percentages of protein used at the laboratory level, starting from the postlarvae stage, giving an explanation on the importance of a balanced feed at 40% protein, to analyze the advantages in growth and production costs, mentioning the importance of a good feeding at this stage of their larval cycle and the different combinations of ingredients to verify a balanced feed that contains essential ingredients such as lipids, proteins, vitamins and minerals to be able to verify a balanced feed that contains essential ingredients such as lipids, proteins, vitamins and minerals to be able to produce a balanced feed that contains essential ingredients such as lipids, proteins, vitamins and minerals to be able to produce a balanced feed, proteins, vitamins and minerals in order to provide a quality feed for the postlarvae and the benefit of varying balanced diets and diets with live feed, which translates into better profitability for producers in this area.
El cultivo del camarón Litopenaeus vannamei cumple un papel muy importante en la economía del Ecuador, ya que genera empleos a muchas familia, el cultivo a nivel de laboratorio es de gran relevancia y muy complejo, ya que se debe controlar muchos factores importantes para el desarrollo de los organismos, entre los cuales se encuentran los parámetros físicos, químicos y biológicos, esta revisión bibliográfica se enfoca en analizar la relación entre los parámetros antes mencionados para una mejor supervivencia y crecimiento, además de enfatizar la importancia del alimento balanceado en las postlarvas de camarón Litopenaeus vannamei dando a conocer los porcentajes de proteína que se utilizan a nivel de laboratorio, iniciándose desde la etapa de postlarva, otorgando una explicación sobre la importancia del balanceado al 40% de proteína, para analizar las ventajas en el crecimiento y en los costos de producción, mencionando la importancia de una buena alimentación en esta etapa de su ciclo larval y las distintas combinaciones de ingredientes para verificar un balanceado que contenga ingredientes esenciales como lípidos, proteínas, vitaminas y minerales para poder suministrar una alimentación de calidad para las postlarvas y el benefició de variar dietas de balanceado y dietas con alimento vivo, lo que se traduce en una mejor rentabilidad para los productores que se dedican a esta área.
Keywords: POSTLARVA; NUTRICION; BALANCEADO